The black citizen-subject: black single mothers in US military recruitment material. Issue 14 (13th November 2016) - Christensen, Wendy M.
ABSTRACT: This article examines how the US military uses race inequalities to mobilize black single mothers for enlistment of their children in the Armed Forces. Through an analysis of military recruitment materials during the height of the US War on Terrorism, I demonstrate how the military disproportionately shows black single mothers going through a process of reacting to their child's enlistment (with fear and worry), welcoming the military institution as the co-parent, and accepting enlistment as a venue for education and career opportunities (productive citizenship). The military models a citizen-mother who supports their child's enlistment, while unquestionably supporting the war. This exploits the obligations of citizenship for black single mothers, whose citizenship is already under scrutiny. By targeting the children of these mothers for recruitment, the military encourages a higher burden of military participation on an already underprivileged segment of the population.